Natural high forest cover dynamics in Aweta River watershed: A case of Southern Ethiopia - Gemmechis, Wendafiraw Abdisa (Journal of Forests, 2025)
Natural forest cover change for commercial and non-commercial purposes affects the forest itself and forest agents. The main aim of this study was to assess land cover change focusing on Anferara natural forest, located in the Awata River Watershed of Southern Ethiopia, over the past 38 years. Land use and land cover classification was performed using Google Earth Engine and utilized the random forest classifier. Landsat TM data for 1985 and 1994, Landsat ETM+ for 2004, Landsat 8 (OLI) for 2014, and Sentinel-2 for 2023 were used. The overall accuracy assessments of all study years were greater than 96%. The results of the land use and land cover change classification reveal an increase in shrubland, which occupies large areas formerly covered by natural forest. This indicates that the arid and semi-arid land in Southern Ethiopia has expanded over time, primarily due to drought and anthropogenic barriers. Conversely, forest land decreased significantly from 433.8 square kilometers in 1985 to 79 square kilometers in 2023. Meanwhile, there was a notable increase in shrubland, agricultural land, settlement areas, and wetlands, from 3.18, 1.66, and 6.5 square kilometers in 1985 to 60.33, 98.4, and 38.78 square kilometers in 2023, respectively. The deforestation rate in the Awata River Watershed was approximately 67.58 square kilometers per year. Based on historical data and oral information, the deforestation in the area is primarily attributed to drought and other anthropogenic barriers.